Inhibition of the Inflammasome Activity of NLRP3 Attenuates HDM-Induced Allergic Asthma - Ma, Ming; Li, Guoyang; Qi, Minghui; Jiang, Wei; Zhou, Rongbin (Frontiers in Immunology, 2021)
Inhaled allergens promote inflammatory response, tissue damage, and airway hyperresponsiveness in the lungs, leading to allergic asthma. NLRP3, as an immune sensor of infections and cellular stress, is associated with the development and exacerbation of asthma. However, the mechanism by which NLRP3 affects asthma requires further investigation. Here, we showed that inhaled house dust mite (HDM) promotes NLRP3 inflammasome activation in the lungs and specifically induces the maturation of caspase-1 and IL-1β in alveolar macrophages (AMs). Using Nlrp3-mutant mice, we found that NLRP3 promotes the inflammatory response and pathogenesis in HDM-induced allergic asthma in an inflammasome-dependent manner. Treatment with RRx-001, an NLRP3 inhibitor, significantly reduced inflammatory cell infiltration and mucus secretion in the airway. Our results showed that NLRP3 in myeloid cells promoted the development and progression of allergic asthma in an inflammasome-dependent manner. Small molecules targeting the NLRP3 inflammasome may provide new treatment options for this disease.